Hand-held echocardiography: added value in clinical cardiological assessment - Ballo Piercarlo; Zacà Valerio; Barbati Riccardo; Galderisi Maurizio; Mondillo Sergio; Giannotti Giovanna; Agricola Eustachio; Guerrini Francesco (Cardiovascular Ultrasound, 2005)
Abstract Background The ultrasonic industry has recently produced echocardiographic Hand Held Devices (miniaturized, compact and battery-equipped echocardiographic systems). Their potential usefulness has been successfully assessed in a wide range of clinical conditions. The aim of the study was to verify if the routine use of a basic model of echocardiographic Hand Held Device (HHD) could be an important diagnostic tool during outpatient cardiologic consulting or in non-cardiologic hospital sections. Methods 87 consecutive patients were included in this study; they underwent routine physical examination, resting ECG and echocardiographic evaluation using a basic model of HHD performed by trained echocardiographists; the cardiologist, whenever possible, formulated a diagnosis. The percentage of subjects in whom the findings were judged reasonably adequate for final diagnostic and therapeutic conclusions was used to quantify the "conclusiveness" of HHD evaluation. Successively, all patients underwent a second echocardiographic evaluation, by an examiner with similar echocardiographic experience, performed using a Standard Echo Device (SED). The agreement between the first and the second echocardiographic exam was also assessed. Results Mean examination time was 6.7 ± 1.5 min. using HHD vs. 13.6 ± 2.4 min. using SED. The echocardiographic examination performed using HHD was considered satisfactory in 74/87 patients (85.1% conclusiveness). Among the 74 patients for whom the examination was conclusive, the diagnosis was concordant with that obtained with the SED examination in 62 cases (83.8% agreement). Conclusion HHD may generally allow a reliable cardiologic basic evaluation of outpatient or subjects admitted to non-cardiologic sections, more specifically in particular subgroups of patients, with a gain in terms of time, shortening patient waiting lists and reducing healthy costs.